The French Tax System Main Characteristics, Recent Developments and Some Considerations for Reform - Leibfritz, Willi (OECD Publishing, 2005)
France belongs to the group of OECD countries with relatively high tax levels. In recent years French governments have been increasingly aware that the tax system may have negative effects on growth and employment and some reforms have been introduced to reduce tax distortions. There has, however, been no grand reform design and it is also not clear in which direction it should go. This paper describes the main characteristics and the developments of the French tax system and examines some of its economic distortions and complexities. A future tax reform agenda could focus on the following five elements: First, reduce labour tax distortions by further reductions in social security contributions for low paid workers and reducing the withdrawal rate for in-work benefits, financing these either by increasing the Contribution Sociale Généralisée (CSG) or value added tax. Second, simplify the personal income tax, widening its base to permit lower top rates, and introducing deduction at source. Consider merging it with the CSG if this can be done in an administratively efficient way. Third, reduce capital tax distortions by cutting the corporate tax rate and widening the tax base by reducing the number of special incentives for certain kinds of activity, and also reduce the bias in favour of debt finance. Fourth, increase the role of "green" taxes because of the efficiency gains they offer -- though not as significant sources of revenue. Fifth, improve, and reduce the costs of, tax administration by progressively merging tax administrations where possible. This Working Paper relates to the 2005 OECD Economic Survey of France (www.oecd.org/eco/surveys/france)
Keywords: Economics; France